Tracking cortical excitability dynamics with transcranial magnetic stimulation in focal epilepsy. Issue 4 (17th March 2022) - Helling, Robert M.; Shmuely, Sharon; Bauer, Prisca R.; Tolner, Else A.; Visser, Gerhard H.; Thijs, Roland D.
Abstract: Introduction: The lack of reliable biomarkers constrain epilepsy management. We assessed the potential of repeated transcranial magnetic stimulation with electromyography (TMS‐EMG) to track dynamical changes in cortical excitability on a within‐subject basis. Methods: We recruited people with refractory focal epilepsy who underwent video‐EEG monitoring and drug tapering as part of the presurgical evaluation. We performed daily TMS‐EMG measurements with additional postictal assessments 1–6 h following seizures to assess resting motor threshold (rMT), and motor evoked potentials (MEPs) with single‐ and paired‐pulse protocols. Anti‐seizure medication (ASM) regimens were recorded for the day before each measurement and expressed in proportion to the dosage before tapering. Additional measurements were performed in healthy controls to evaluate day‐to‐day rMT variability. Results: We performed 77 (58 baseline, 19 postictal) measurements in 16 people with focal epilepsy and 35 in seven healthy controls. Controls showed minimal day‐to‐day rMT variation. Withdrawal of ASMs was associated with a lower rMT without affecting MEPs of single‐ and paired‐pulse TMS‐EMG paradigms. Postictal measurements following focal to bilateral tonic–clonic seizures demonstrated unaltered rMT and increased short interval intracortical inhibition, while measurements following focal seizures with impaired awareness showed decreased rMT's and reduced short and long interval intracortical inhibition. Conclusion: Serial within‐subject rMT measurements yielded reproducible, stable results in healthy controls. ASM tapering and seizures had distinct effects on TMS‐EMG excitability indices in people with epilepsy. Drug tapering decreased rMT, indicating increased overall corticospinal excitability, whereas seizures affected intracortical inhibition with contrasting effects between seizure types.